2019
DOI: 10.1038/s41598-019-54591-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive multivariate correlations between climatic effect, metabolite-profile, antioxidant capacity and antibacterial activity of Brazilian red propolis metabolites during seasonal study

Abstract: The standardization of apiceutical products like as propolis extracts has been widely debated worldwide and variations in the propolis chemical composition are still very relevant topics for use-standardized of different propolis-type as medication by much of the world’s population. The present manuscript discuss important issues related to the climate effect and variations in propolis metabolite-profiling changes, antioxidant capacity and variations of the antibacterial activity of the Brazilian red propolis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 85 publications
2
40
0
7
Order By: Relevance
“…Several abiotic factors such as light intensity, average temperature, humidity, wind speed, solar radiation, water availability, and rainfall, collectively defined as seasonal effects, can directly affect the concentration of plant components, including flavonoids and phenolic acids, which influence the chemical composition and bioactivity of propolis [61][62][63]. This aspect poses difficulties propolis classification and standardization, and the different solvents and extraction methods may influence its activity [32,64].…”
Section: Turkeymentioning
confidence: 99%
“…Several abiotic factors such as light intensity, average temperature, humidity, wind speed, solar radiation, water availability, and rainfall, collectively defined as seasonal effects, can directly affect the concentration of plant components, including flavonoids and phenolic acids, which influence the chemical composition and bioactivity of propolis [61][62][63]. This aspect poses difficulties propolis classification and standardization, and the different solvents and extraction methods may influence its activity [32,64].…”
Section: Turkeymentioning
confidence: 99%
“…In previous studies of propolis from the Sonoran Desert, we found that the antiproliferative effect of UP in human and murine cancer cell lines, such as M12.C3.F6, was clearly influenced by collection time [ 19 , 20 ]. These seasonal variations are additionally supported by recent studies that have established a correlation between total phenolic compounds in Brazilian red propolis and meteorological parameters throughout the year, such as rainfall intensity, relative humidity and solar radiation, conditions that modulate the biosynthesis of polyphenols in selected plants, and therefore determine the pharmacological potential of seasonal propolis [ 18 ]. Other studies also reported seasonal differences in the antimicrobial activity of red propolis collected during seasons with rainy and dry periods, observing quantitative differences in chemical composition and supporting the variability of propolis biological activities throughout the year [ 47 ].…”
Section: Discussionmentioning
confidence: 75%
“…The broad array of biological activities of propolis include antioxidant, antibacterial, antiparasitic, antifungic, immunomodulatory activity and antiproliferative effects, among others [ 10 , 12 , 13 , 14 , 15 , 16 , 17 ]. At present, the seasonal influence on propolis production from dissimilar geographical areas, as well as derived from different plant origins, has been studied to establish a correlation between its pharmacological potential and the qualitative and quantitative fluctuations of propolis constituents throughout the year [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of botanical origins and chemical compositions of propolis from a wide range of countries revealed that the antibacterial activity was attributed to samples from locations featuring a wet-tropical rainforest-type climate [40]. The antioxidant and antibacterial activities of the Brazilian red propolis were influenced by climatic variations [41]. Due to the different climatic and vegetation characteristics, a distinct classification of Argentinian propolis between the coastal region and the top of the mountain region was shown by a digital image-based traceability tool [42].…”
Section: Discussionmentioning
confidence: 99%